Synthesis and Characterization of Carbon Nanomaterial Derived from Anthracite. (2020) - Maria, Santhi; singh, Shraddha; Pandey, Mayank; Manoj, B.
Abstract: Among various storage devices, carbon based supercapacitors grabs the recent trends in the electronic devices. The present research work describes the synthesis of carbon nanomaterials derived from anthracite by using staudenmaier method. Anthracite was used as a precursor because of its high carbon content. The structural and chemical complex formation carried out by using XRD and FTIR confirms the formation of CNT's. The calculated value obtained from the XRD peaks confirms the formation of multilayer carbon nano-materials. The electrode was prepared by coating synthesized CNT on copper rod. The electrochemical performance of prepared working electrode was carried out by using cyclic voltammetric performance. Electrode characterization was performed for different scan rates 10, 20, 30 and 50 mV/sec in a potential window from -0.08 to 0.2V. The CV curves represents symmetric nature which imply that electrode material have stable capacitive process